Understanding unfolding and refolding of the antibody fragment (Fab). I. In-vitro study - Gani, Kayanat; Bhambure, Rahul; Deulgaonkar, Prashant; Mehta, Deepa; Kamble, Manoj (Biochemical Engineering Journal, 2020)
In-vitro protein refolding is a major rate-limiting step in the large scale production of antibody fragments expressed using a microbial source like E. coli. This investigation is focused on understanding the in-vitro unfolding and refolding of the multi-domain protein involving inter-domain disulfide linkage, like antibody fragment (Fab). Solubilization behavior of the inclusion bodies and unfolding events of Fab fragment (Biosimilar rHu Ranibizumab) were studied using nano-differential scanning fluorimetry (nano-DSF). Fab unfolding behavior was studied by fitting experimental data with the two-state and three-state thermodynamic model. Based on the Fab unfolding understanding, a two-stage design of experiment (DoE) strategy was used for the optimization of the in-vitro refolding condition of a Fab fragment. Refolding yield of 56.03 +/- 1.15 % was achieved using the optimized oxidative refolding conditions maintained by appropriate dilution factor and redox reagent ratio. Refolding kinetics of the rHu Ranibizumab was analyzed using a three-parameter kinetic model showing rate constant k(1) :7.05e(-6) l/mg.min, k(2) :0.57 l/mg.min, and k(3) :310.19 l/mg.min. Based on observed refolding kinetics, it was concluded that the Fab refolding follows a three-state mechanism with the refolding intermediate/(s) formation from light and heavy chain of the Fab fragment as an overall rate-limiting step. The method described here is a useful tool to identify high-yield scalable refolding conditions for multi-domain proteins involving inter-domain disulfide bonds.
Keywords: Antibody fragment; In-vitro refolding; Refolding kinetics; rHu Ranibizumab; Two-state and Three-state models